The last stand of Fox Company : [compact disc, unabridged] : a true story of U.S. Marines in combat - Drury, Bob (Tantor Audio ; Distributed by Recorded Books, 2009)
Drury offers the story of the courageous mission of the Marines of Fox Company who found themselves surrounded and greatly outnumbered by Chinese forces at the Chosin Reservoir in North Korea.